Utilization of Authentic Assessments in General Chemistry 2: Its Correlation on Students' Learning Experience - Mellona, Jonathan; Ancheta, Cristo Mark D. (Future Science / FSH-PH Publications, 2025)
Assessment plays a significant role in enhancing the teaching and learning process, serving as a tool to gauge students’ understanding and guide instructional improvement. However, traditional assessments in science education often emphasize rote memorization rather than conceptual understanding and real-world application. This study investigated the relationship between the utilization of authentic assessments in General Chemistry 2 and students’ learning experience among Grade 12 STEM students at Pasig National High School, during the first semester, S.Y. 2025–2026. Utilizing a descriptive-correlational research design, data were collected from 80 randomly selected respondents through a structured questionnaire. Descriptive statistics revealed that authentic assessments are frequently used in their General Chemistry 2 class. Moreover, Grade 12 STEM students demonstrated a highly positive learning experience in terms of learning engagement, conceptual understanding and perceived real-life relevance. Meanwhile, inferential statistics using Pearson’s correlation showed a significant relationship between utilization of authentic assessments in General Chemistry 2 and students’ learning experience, with weak to moderate positive correlations (r values ranging from 0.254 to 0.657, p<0.05). These findings imply that as the utilization of authentic assessments in Chemistry class increases, the students’ learning experiences also increases. Furthermore, it is recommended that science teachers continuously integrate and diversify authentic assessments to promote reflection, collaboration, and critical thinking. Additionally, teacher training programs should emphasize on designing rubrics and validating authentic assessment that align with the K–12 science curriculum competencies, thereby preparing learners for real-world problem-solving and lifelong learning.